Teaching-learning relationship and the impossibility of education - Anacleto, Julia Maria Borges (Clinical Styles. The Journal on the vicissitudes of childhood, 2016)
This article questions the hegemonic pedagogical discourse and its search for adapting the teaching process to the "student reality" in order to guarantee their learning. Such reality is now presented as cognitive, then as social, and also as affective. Aiming at sustaining the learning process as an effect of the (dis)encounter between master and pupil, we have taken psychoanalysis as a discourse capable not of reinforcing the adapting illusion (as seen in many attempts to apply psychoanalysis to education), but in the sense of affirming the impossible character of educating, and thus paradoxically instigating teachers not to renounce education.